Accurate thermal sensing with modern CMOS integrated circuits : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Auckland, New Zealand - Fisk, Robert Patrick (Massey University, 2010)
Digital control systems can be found performing a wide range of duties throughout modern society. These systems demand accurate, low cost interfaces to physical parameters of interest, one of the most common being temperature. A ‘smart’ sensor takes advantage of modern integrated circuit technology to create a sensor and analog-to-digital converter on the same silicon chip. Smart temperature sensors are widely available offering simple digital interfaces, high reliability, low power consumption and low cost. The primary weakness of these devices is the low inherent accuracy of on-chip thermal sensors. This thesis presents a smart thermal sensor design that improves upon current technology by employing a modern 0.13μm CMOS process and circuit-level techniques to reduce sensor size and power consumption while increasing digital converter resolution. Data is presented that shows uncalibrated sensor accuracy can be increased by using correlated device characteristics to compensate for random inter-device variation. The research findings guide the construction of future smart thermal sensors with uncalibrated accuracy levels exceeding that of any currently available design.
Content removed due to copyright Conference Proceedings I R. P. Fisk and S. M. Hasan, “Analysis of Internally-Generated Noise in Bandgap References,” in Proc. Electronics New Zealand Conf., Christchurch, New Zealand, Nov. 2006, pp. 18-23. Conference Proceedings II R. P. Fisk and S. M. Hasan, “Incremental Delta-Sigma Modulators for Temperature Sensing Applications,” in Proc. Int. Conf. Mechatronics and Machine Vision in Practice, Auckland, New Zealand, Dec. 2008, pp. 63-67. Conference Proceedings III R. P. Fisk and S. M. Hasan, “Low-Cost Temperature Sensor on a Modern Submicron CMOS Process,” in Proc. Electronics New Zealand Conf., Otago, New Zealand, 2009, pp. 43-48.
Keywords: Digital control systems; Smart sensors; Fields of Research::290000 Engineering and Technology::299900 Other Engineering and Technology::299904 Engineering/technology instrumentation